Analisis Kepuasan Petani Terhadap Kegiatan Penyuluhan Pertanian di Kelurahan Kalampangan, Kota Palangka Raya Kalimantan Tengah: Farmer Satisfaction Analysis Of Agricultural Extension Activities In The Village Kalampangan, The City Of Palangkaraya Central kalimantan - Berkat, Berkat; Sunaryati, Revi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2015)
This research is aimed at to know the satisfaction of farmer about farming extesionactivities at Village Kalampangan. The data were collected 42 sample farmers through questionrurires.Then the data were analyzed by using descriptive and nonparametric statistics it’s the spearman correlation. The results of research showed thatfarmer satisfaction about farming extesion activities has satisfed category. Dimensions of quality serttices that’s tangible, reliability, responseiveness, assurctnce, and empatlry, was positive coruelation with farmer satisfaction at village Kalampangan, Palangko Raya city.